Pengaruh Inovasi, Diversifikasi, Fleksibilitas, Informasi, dan Kewirausahaan Terhadap Kinerja Usaha Mikro Kecil dan Menengah di Kabupaten Pamekasan - Risal, Zef; Gazali, Gazali; Hakim, Rachman; Furqon, Muhammad Amir; Bustaram, Isnain; Kusuma, Adriani; Zainurrafiqi, Zainurrafiqi; Hidayati, Nurul (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2024)
This study specifically examines the influence of five main internal factors, namely innovation, diversification, error, information, and entrepreneurship, on the performance of Micro, Small and Medium Enterprises (MSMEs) in Pamekasan Regency. This study uses an explanatory quantitative approach with the aim of deeply understanding the influence of each internal factor on MSME performance. The research sample involved 400 MSME actors who were randomly selected from various business sectors in Pamekasan Regency, including trade, services, manufacturing, and other sectors. Data were collected through a questionnaire designed to measure the dimensions of the five independent variables and the MSME performance variable as the dependent variable. Data analysis was carried out using SPSS software to ensure the accuracy and validity of the results obtained. The results of the multiple linear regression analysis showed that each independent variable had a significant influence on MSME performance. Innovation contributes greatly to increasing the competitive advantage of MSMEs through the creation of new, relevant products and services that are in accordance with the needs of the ever-growing market. Diversification was also found to have a significant influence, where MSMEs that have a variety of products or services tend to be more resistant to economic risk and are able to maintain business stability in fluctuating market conditions. Flexibility, as the ability of MSMEs to adapt to changes in the business environment, shows a positive influence on MSME performance, especially in dealing with rapid changes in consumer preferences. Meanwhile, information plays an important role in supporting strategic decision-making, by enabling MSMEs to have access to accurate market data and trends. Finally, entrepreneurship has a significant impact on MSME performance, because the proactive, creative, and innovative attitudes of business actors are able to open up new opportunities and strengthen the position of MSMEs in the market